Pre-game hydration status, sweat loss, and fluid intake in elite Brazilian young male soccer players during competition - da Silva, R. P.; Mündel, T.; Natali, A. J.; Bara Filho, M. G.; Alfenas, R. C. G.; Lima, J. R. P.; Belfort, F. G.; Lopes, P. N. R.; Marins, J. C. B. (Journal of Sports Sciences, 2011)
In this study, we assessed the pre-game hydration status and fluid balance of elite young soccer players competing in a match played in the heat (temperature 31.0 ± 2.0°C, relative humidity 48.0 ± 5.0%) for an official Brazilian soccer competition. Fluid intake was measured during the match, as were urine specific gravity and body mass before and after the game to estimate hydration status. Data were obtained from 15 male players (age 17.0 ± 0.6 years, height 1.78 ± 0.06 m, mass 65.3 ± 3.8 kg); however, data are only analysed for 10 players who completed the full game. The mean (±s) sweat loss of players amounted to 2.24 ± 0.63 L, and mean fluid intake was 1.12 ± 0.39 L. Pre-game urine specific gravity was 1.021 ± 0.004, ranging from 1.010 to 1.025. There was no significant correlation between sweat loss and fluid intake (r = 0.504, P = 0.137) or between urine specific gravity and fluid intake (r = -0.276, P = 0.440). We conclude that young, native tropical soccer players started the match hypohydrated and replaced about 50% of the sweat lost. Thus, effective strategies to improve fluid replacement are needed for players competing in the heat.